Perencanaan Kurikulum PAI Di Sekolah Dan Madrasah - syifa, Sunariyah; Agus Pahrudin, Agus Jatmiko; Koderi, Imam Syafe’i (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The curriculum planning of Islamic Religious Education (PAI) in schools and madrassas is a fundamental aspect in realizing an education system that is oriented towards the formation of noble morals, character strengthening, and moderate religious understanding. The problem raised in this study is how the PAI curriculum planning is structured to be relevant to the times, the needs of students, and still in line with Islamic values and national education policies. This research uses the library research method, with data collection techniques through literature review from various sources such as academic books (PAI Curriculum Development, 2023 and 2025 editions), scientific journals in 2021-2025, laws and regulations, and relevant curriculum documents. The data was analyzed descriptive-qualitatively through the process of data reduction, thematic classification, and content interpretation to explore the concepts, principles, and practices of PAI curriculum planning.The purpose of this study is to examine and describe the ideal PAI curriculum planning and the factors that affect it in the context of schools and madrasas. The results of the study show that effective PAI curriculum planning must be based on the integration between philosophical, psychological, pedagogical, and socio-cultural aspects. The involvement of teachers, principals, and related parties is key in developing an adaptive and applicable curriculum. The urgency for the next researcher is to conduct field research to assess the implementation and effectiveness of the curriculum planning that has been prepared, as well as explore innovative approaches in aligning PAI with the challenges of globalization and digitalization of education.